Integration of Agricultural Automation, and Sustainable Tourism Businesses to Strengthen the Green Economy, and Achieve Food Self-Sufficiency in Wonosalam Village - Agus Sukoco; Achmad Muchayan; Fetty Asmaniati; Nuryadi Nuryadi; Muhammad Ikhsan Setiawan; Che Zalina Zulkifli; Fazilat Kodirova (International Journal of Engineering, Science and Information Technology, 2026)
The transition toward a green economy requires rural communities to adopt innovative strategies that integrate sustainable agriculture, technological advancement, and tourism-based economic development. Wonosalam Village in Jombang Regency, Indonesia, possesses considerable potential to support this transformation due to its fertile agroforestry landscapes, abundant biodiversity, agricultural productivity, and rapidly growing eco-tourism sector. This study examines the synergistic integration of agricultural automation and sustainable tourism as a strategic approach to improving food self-sufficiency, increasing rural income, and strengthening the local green economy. The research employs a mixed-methods approach, combining field surveys, participatory rural appraisal, direct observation, and stakeholder interviews involving farmers, tourism operators, local government officials, and community leaders. In addition, pilot implementations of small-scale automation technologies were conducted in horticultural and livestock production systems to assess their operational effectiveness and socio-economic impact. The findings indicate that the adoption of smart farming technologies, including automated irrigation systems, precision nutrient delivery, environmental monitoring sensors, and solar-powered post-harvest processing facilities, significantly improves resource efficiency, productivity, and product quality while reducing production costs and environmental pressures. Furthermore, the integration of agricultural activities with tourism experiences creates diversified income opportunities through farm-based recreation, agrotourism attractions, local product marketing, and educational programs focused on sustainable farming practices. The model also supports the principles of a circular economy by utilizing agricultural by-products as resources for tourism activities, organic fertilizer production, and environmental conservation initiatives. Community participation and stakeholder collaboration were identified as key factors for successful implementation. Overall, the study demonstrates that the integration of agricultural automation and sustainable tourism can enhance rural economic resilience, promote environmental sustainability, and contribute to the development of secure and sustainable food systems. The proposed model offers a practical and replicable framework for other rural regions seeking to achieve green economic growth and long-term community prosperity